All activity-oriented approach in teaching geometry - Milo, Gracia Agilada 1949- (1986)
This study compared two third year classes, one taught by an activity-oriented method, the other through traditional non-activity approach using lectures, question and answer type, rules and procedure. It determined the relative effects of the two methods on the achievement and attitude of students in Geometry.
Thesis (M.A.T.)--University of the Philippines, Diliman.
Vita.
Keywords: Geometry -- Study and teaching